Paradiplomatie et finance climatique mondiale : Les cas du Québec, de la Wallonie et de l’Écosse - Annie Chaloux; Gabriel Grégoire-Mailhot; Simon Beaudoin (VertigO)
The adoption of the United Nations Framework Convention on Climate Change (UNFCCC) in 1992 marked a seminal moment for climate governance. The UNFCCC has since played a central role in coordinating efforts to address the challenge of climate change. Among the principles of the UNFCCC that have generated much discussion, the principle of common but differentiated responsibility recognizes the historical responsibility of developed countries for climate change. The latter, having for the most part contributed significantly to greenhouse gas (GHG) emissions, are obliged to reduce their emissions, to support adaptation and resilience to climate change and to facilitate the efforts of other countries in this regard. The latter responsibility includes the transfer of technology and know-how, capacity building and financial support. This article looks at the issue of financing and studies one of the under-documented sources of global climate finance: the role of sub-national entities and non-central governments, such as provinces, regions, or other administrative scales. More specifically, and through the study of three actors particularly active in climate finance and paradiplomacy, namely Quebec, Scotland and Wallonia, we answer the following question: what is the role played by non-central governments in global climate finance? The article offers a detailed descriptive analysis of the three cases and their contributions. Despite the modest sums allocated by these entities, our results suggest that these contributions are a noteworthy step forward and support the relevance of reflecting on the growing role that these actors can play in global climate finance by stimulating broader and more meaningful contributions.